From a Machine Saw to a Case of Pyomyositis - Tejave Sharifan MD; Nosakhare Idemudia MS; Rupam Sharma MD; Arash Heidari MD; Alan Ragland DO; Tom Chao MD; Isabel Fong PharmD (SAGE Publishing, 2022)
Pyomyositis is a bacterial infection occurring mainly in skeletal muscles. It is most commonly caused by Staphylococcus aureus with initial symptoms including muscle pain, swelling, and site tenderness. When available, the most accurate technique to determine the extent and the specific location of disease is the magnetic resonance imaging. Successful management includes early recognition, timely surgical debridement or drainage, and appropriate antibiotic therapy. This case report describes a case of Mycobacterium fortuitum pyomyositis in an elderly male associated with challenges of successful diagnosis.